T Cell Response to Infliximab in Exposed Patients: A Longitudinal Analysis - Pratesi, Sara; Nencini, Francesca; Grosso, Francesca; Dies, Laura; Bormioli, Susanna; Cammelli, Daniele; Maggi, Enrico; Matucci, Andrea; Vultaggio, Alessandra; , ABIRISK Consortium (Frontiers in Immunology, 2019)
This study aimed to evaluate the proportion of infliximab (IFX)-exposed patients exhibiting cellular response to the drug in a longitudinal way and to establish whether it is predictive for anti-drug antibodies (ADA) development. Seventeen patients suffering from immuno-mediated disorders were enrolled. Blood was sampled at baseline and before each of the first eight infusions of IFX. The proliferation of PBMCs to 15-mer peptides covering VH/VL frames of IFX was assessed as well as transcription factors and cytokines mRNA expression of memory T cells in IFX-stimulated PBMCs. The number of peptides recognised by T cells after four infusions was higher than those recognised by the same patients before treatment. IFX-stimulated PBMCs from more than 90% of patients were able to express the main regulators and adaptive cytokines of memory T cells. While IFN-γ mRNAs increased after the first infusion and declined during the subsequent ones, IL-10 mRNA was upregulated throughout the treatment. IL-10 was functionally active because its neutralisation improved IFN-γ and IL-13 mRNA expression in vitro. The IL-10/IFN-γ ratio was shown to be lower in patients who developed ADAs solely at the early infusions. IL-10 production consistently preceded or paralleled the IFN-γ onset in ADA- patients, while it was not produced or followed IFN-γ onset in ADA+ patients. In conclusion, this study provides evidence that the majority of exposed patients undergo a cellular response to IFX with the upregulation of IL-10. The development of ADA is associated with the early impairment of IL-10 and low levels of the IL-10/IFN-γ ratioNFLIXIMABnfliximab